2020
DOI: 10.18235/0002490
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Lockdowns and Domestic Violence: Evidence from Two Studies in Argentina

Abstract: Any dispute related to the use of the works of the IDB that cannot be settled amicably shall be submitted to arbitration pursuant to the UNCITRAL rules. The use of the I DB's name for any purpose other than for attribution and the use of the I DB's logo shall be subject to a separate written license agreement between the IDB and the user agreement between the IDB and the user and is not authorized as part of this CC-IGO license.Note that the link provided above includes additional terms and conditions of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
77
3
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 31 publications
10
77
3
5
Order By: Relevance
“…This finding is inconsistent with the results of some studies based on the effect of external stress on MS reduction ( Maltas, 1992 ; Neff and Karney, 2009 , 2017 ; Randall and Bodenmann, 2009 ; Chi et al, 2011 ). New studies on the effects of coronavirus and lockdown outbreaks on family interactions have shown that the lockdown has weakened the marital interactions by increasing the rate of unemployment and reducing access to financial resources ( Coibion et al, 2020 ), especially in troubled couples ( Perez-Vincent et al, 2020 ). The findings by Kevin and Risla (2020) indicated the association between low income and reduced MS, especially in distressed couples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is inconsistent with the results of some studies based on the effect of external stress on MS reduction ( Maltas, 1992 ; Neff and Karney, 2009 , 2017 ; Randall and Bodenmann, 2009 ; Chi et al, 2011 ). New studies on the effects of coronavirus and lockdown outbreaks on family interactions have shown that the lockdown has weakened the marital interactions by increasing the rate of unemployment and reducing access to financial resources ( Coibion et al, 2020 ), especially in troubled couples ( Perez-Vincent et al, 2020 ). The findings by Kevin and Risla (2020) indicated the association between low income and reduced MS, especially in distressed couples.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of the COVID-19 pandemic as an external stress has challenged the quality of couples’ relationships; home quarantine with negative psychological effects, such as anxiety, stress, depression, and frustration ( Brodeur et al, 2020 ; Idoiaga Mondragon et al, 2020 ), and making changes in the unemployment rate and reducing access to financial opportunities ( Coibion et al, 2020 ), forcing distress couples to spend many hours of the day together and increase the capacity for marital conflicts ( Perez-Vincent et al, 2020 ), can have negative effects on couples’ relationships; these effects become more destructive due to different backgrounds, such as low economic quality and low levels of vulnerability ( Pietromonaco and Overall, 2020 ). Kevin and Risla (2020) showed that couples with low income reported low MS during the lockdown or distressed couples experience worse individual and dyadic outcomes in the face of external stress ( Beach et al, 1994 ).…”
Section: Introductionmentioning
confidence: 99%
“…D A comment on gender-based violence in South Africa during Interestingly, while many other countries observed spikes in gender-based violence (GBV) during COVID-19 lockdown periods (Agüero, 2020;Anderberg et al, 2020;Boserup et al, 2020;Bullinger et al, 2020;Leslie and Wilson, 2020;Mahmud and Riley, 2020;Perez-Vincent et al, 2020;Ravindran and Shah, 2020;Silverio-Murillo et al, 2020), the emerging evidence from telephonic reporting and counselling services, as well as police data, suggests that there was no such increase in GBV during the lockdown in South Africa (Gould, 2020). This is in spite of the fact that the South African lockdown (Level 5 + Level 4) was one of the strictest worldwide and lasted for 66 days.…”
Section: C21 Comparison Of 2020 With 2019mentioning
confidence: 99%
“…The COVID-19 pandemic is still at the center of global attention (Perez-Vincent et al, 2020;Setiati & Azwar, 2020;Sharma et al, 2020). The increase in the number of people with COVID-19 every day will certainly cause anxiety even though the governments of each country have established policies that are preventive, curative and rehabilitative (Oguntayo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Cases of violence against women have also increased. This is influenced by several factors, such as personal and community factors (Perez-Vincent et al, 2020;Sharma et al, 2020). This systematic review study aims to identify the factors that influence the increase in the incidence of violence against women during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%